PERAN GURU DALAM MENGEMBANGKAN KARAKTER CINTA TANAH AIR SISWA DI SMP NEGERI 12 BANJARMASIN - Eka Putri, Regina; Agus Ruchliyadi, Dian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the suboptimal character of patriotism among students at SMP Negeri 12 Banjarmasin, which is evident in the lack of discipline, concern for the environment, and the influence of external culture and social media. This study aims to describe the role of teachers in developing students' patriotism and identify the obstacles faced at SMP Negeri 12 Banjarmasin. This study uses a qualitative approach with a descriptive research type. Data collection techniques through interviews, observation, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results show that teachers at SMP Negeri 12 Banjarmasin play an important role in developing the character of patriotism as role models, facilitators, and motivators. As role models, teachers demonstrate attitudes and behaviors of discipline, politeness, compliance with rules, and involvement in school activities such as flag ceremonies and national holiday commemorations. As facilitators, teachers create active learning through media, discussions, concrete examples, and direct practice. As motivators, teachers provide encouragement through advice, discussions, real examples, direct involvement, and guidance to foster student awareness. However, there are obstacles, including family background, low student awareness, social media and foreign culture, and a lack of student interest. It is recommended that teachers increase their role as role models, facilitators, and motivators in developing students' patriotism.